Robot berbasis Multi Independent Steering System untuk Membantu Penyandang Tuna Daksa - Anita Fitrizia (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2015)
Abstract - Open research in the field of robotics encourages individual creativity to create creative solutions to help people with disabilities. Robots are technologies that can relieve or replace human power. The need to provide food for persons with disabilities is very important because of its limitations. Nurses are the general solution to the limitations of people with disabilities, but what happens in America is a frequent weather problem and brings nurses to help people with disabilities. So you need a tool that can replace the work of a nurse. The solution to this problem is to make robots that can replace several servants' tasks, such as taking, moving and putting food and beverage boxes from one place to another. Robotic maneuverability is an important part of the job. A multi-independent steering system is used to reduce the robot's movement space when maneuvering. Besides being able to maneuver, robots must be able to pick up and transport food and beverage boxes using a gripping system. The success rate of robots completing their assignments reached 93.75% of 112 tests. Keyword : robot, prototype, multi-independent steering, person with dissability